(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes methods for monitoring the population density of lepidopteran pests. Depending on the purpose of the research and the habitat of the pest, monitoring methods such as soil layer examination, the use of special nets, traps, and route control have been developed. Based on the research results, in order to achieve sufficient accuracy when counting lepidopteran insect caterpillars, it is also necessary to study the features of their spatial distribution along the area of the entire field. The use of modern geographic information systems (GIS) in this process, including the establishment of GPS coordinates for each sample taken, the creation of geographic information databases are of great importance in accurately identifying the foci and boundaries of pest distribution, analyzing the characteristics of long-term distribution and in increasing the effectiveness of control measures against them.